2008
DOI: 10.1051/0004-6361:20079150
|View full text |Cite
|
Sign up to set email alerts
|

Point spread function calibration requirements for dark energy from cosmic shear

Abstract: Context. The control of systematic effects when measuring background galaxy shapes is one of the main challenges for cosmic shear analyses. Aims. Study the fundamental limitations on shear accuracy due to the measurement of the point spread function (PSF) from the finite number of stars that are available. We translate the accuracy required for cosmological parameter estimation to the minimum number of stars over which the PSF must be calibrated. Methods. We characterise the error made in the shear arising fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
183
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(186 citation statements)
references
References 23 publications
(38 reference statements)
3
183
0
Order By: Relevance
“…Mellier 1999;Bartelmann & Schneider 2001;Refregier 2003;Hoekstra & Jain 2008;Munshi et al 2008) and has been shown to be the most promising probe of dark energy (Albrecht et al 2006;Peacock et al 2006). Surveys' optimization and systematics minimizations in both software and hardware have been investigated (Heymans et al 2006;Massey et al 2007a;Amara & Réfrégier 2007, 2008Paulin-Henriksson et al 2008;Amara et al 2009;Bridle et al 2009), favoring wide surveys, with well-controlled, stable Point Spread Function, with comprehensive photometric redshift follow-up. Those characteristics are shared by ambitious upcoming large area surveys, such as the Large Synoptic Survey Telescope (LSST) 5 , the Panoramic Survey Telescope & Rapid Response System (Pan-STARRS) 6 , Euclid 7 and the Joint Dark Energy Mission (JDEM) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Mellier 1999;Bartelmann & Schneider 2001;Refregier 2003;Hoekstra & Jain 2008;Munshi et al 2008) and has been shown to be the most promising probe of dark energy (Albrecht et al 2006;Peacock et al 2006). Surveys' optimization and systematics minimizations in both software and hardware have been investigated (Heymans et al 2006;Massey et al 2007a;Amara & Réfrégier 2007, 2008Paulin-Henriksson et al 2008;Amara et al 2009;Bridle et al 2009), favoring wide surveys, with well-controlled, stable Point Spread Function, with comprehensive photometric redshift follow-up. Those characteristics are shared by ambitious upcoming large area surveys, such as the Large Synoptic Survey Telescope (LSST) 5 , the Panoramic Survey Telescope & Rapid Response System (Pan-STARRS) 6 , Euclid 7 and the Joint Dark Energy Mission (JDEM) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the reconstruction can be checked by directly comparing the recovered PSF image and the original star image, in terms of their sizes, ellipticities, or other properties (Hoekstra 2004;Wittman 2005;Van Waerbeke et al 2005;Heymans et al 2012;Hamana et al 2013). The residual PSF ellipticity error can be used to estimate the induced shear recovery error through the shear susceptibility factor (Paulin-Henriksson et al 2008;Rowe 2010) in certain shear measurement methods.…”
mentioning
confidence: 99%
“…In Paulin-Henriksson et al (2008) (P1 hereafter), we investigated the link between systematic errors in the power spectrum and uncertainties in the PSF correction phase. The framework is the following.…”
Section: Introductionmentioning
confidence: 99%